Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1242/jeb.057406
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional characterization of an ovarian aquaporin from the cockroachBlattella germanicaL. (Dictyoptera, Blattellidae)

Abstract: SUMMARYAquaporins (AQPs) are membrane proteins that form water channels, allowing rapid movement of water across cell membranes. AQPs have been reported in species of all life kingdoms and in almost all tissues, but little is known about them in insects. Our purpose was to explore the occurrence of AQPs in the ovary of the phylogenetically basal insect Blattella germanica (L.) and to study their possible role in fluid homeostasis during oogenesis. We isolated an ovarian AQP from B. germanica (BgAQP) that has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 55 publications
2
21
1
Order By: Relevance
“…Aquaporins are indispensable water and solute channels needed to maintain homeostasis in living organisms. In insects, aquaporins relieve pressure imposed by osmotically imbalanced diets, remove excess fluids and excretions, maintain fluid homeostasis during oogenesis, stabilize membranes and enzymes for anhydrobiosis and cryoprotection, are involved in water movement in respiration, and prevent desiccation during molting and egg hatching (Campbell et al, 2008;Drake et al, 2010, Duchesne et al, 2003, Fabrick et al, 2014Goto et al, 2011Goto et al, , 2015Herraiz et al, 2011;Kikawada et al, 2008;Le Cahérec et al, 1997;Liu et al, 2011;Martini et al, 2004;Maruyama et al, 2015;Mathew et al, 2011;Nagae et al, 2013;Philip et al, 2011;Spring et al, 2009;Staniscuaski et al, 2013;Yi et al, 2011). Because of their major importance in these physiological processes, aquaporins may serve as potential targets for insect pest management, especially in phloem-feeding hemipterans where imbibition of large volumes of liquid diet is required to meet nutrient requirements (Douglas, 2006;Ibanez et al, 2014;Mathew et al, 2011;Shakesby et al, 2009;Tzin et al, 2015;Wallace et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aquaporins are indispensable water and solute channels needed to maintain homeostasis in living organisms. In insects, aquaporins relieve pressure imposed by osmotically imbalanced diets, remove excess fluids and excretions, maintain fluid homeostasis during oogenesis, stabilize membranes and enzymes for anhydrobiosis and cryoprotection, are involved in water movement in respiration, and prevent desiccation during molting and egg hatching (Campbell et al, 2008;Drake et al, 2010, Duchesne et al, 2003, Fabrick et al, 2014Goto et al, 2011Goto et al, , 2015Herraiz et al, 2011;Kikawada et al, 2008;Le Cahérec et al, 1997;Liu et al, 2011;Martini et al, 2004;Maruyama et al, 2015;Mathew et al, 2011;Nagae et al, 2013;Philip et al, 2011;Spring et al, 2009;Staniscuaski et al, 2013;Yi et al, 2011). Because of their major importance in these physiological processes, aquaporins may serve as potential targets for insect pest management, especially in phloem-feeding hemipterans where imbibition of large volumes of liquid diet is required to meet nutrient requirements (Douglas, 2006;Ibanez et al, 2014;Mathew et al, 2011;Shakesby et al, 2009;Tzin et al, 2015;Wallace et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In other insects, Prips have a variety of physiological functions. For example, Blattella germanica Prip is present in the adult ovary, fat body, and muscles, and plays a role in fluid homeostasis during oogenesis (Herraiz et al, 2011). The Bombyx mori Prip is found in the oocyte plasma membrane within ovaries and functions during oocyte growth (Maruyama et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, only a very small fraction of insect aquaporins have been functionally characterized by sensitivity to mercuric ions, knockout (aquaporin-deficient) organisms and functional system assays (Kaufmann et al, 2005;Cohen, 2012;Tzin et al, 2015;Van Ekert et al, 2016). Insect Drips (Kaufmann et al, 2005;Raza et al, 2016;Shakesby et al, 2009;Tzin et al, 2015;Van Ekert et al, 2016), Prips (Kikawada et al, 2008;Herraiz et al, 2011;Tzin et al, 2015;Van Ekert et al, 2016) and Eglps (Van Ekert et al, 2016) have been confirmed to be involved in water permeability. Moreover, using in vivo RNA interference (RNAi; knockdown) techniques, inhibitory or modified effects have been documented in plant sap-sucking and blood-feeding insect species (Cohen, 2013;Jing et al, 2016;Van Ekert et al, 2016;Tsujimoto et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The one C. merolae homologue most closely resembles aquaporin‐1 of Bemisia tabaci (Sweet potato whitefly; TC# 1.A.8.8.15) which has specificity for water and perhaps small neutral solutes such as urea (Herraiz et al. , Mathew et al. ).…”
Section: Resultsmentioning
confidence: 99%